Epigallocatechin-3-gallate exerts protective effects against heat stress through modulating stress-responsive transcription factors in poultry - Orhan, C.; Tuzcu, M.; Gencoglu, H.; Şahin, Nurhan.; Hayirli, A.; Şahin, Kazım (Taylor & Francis Ltd, 2013)
1. The aim of the study was to describe the effect of Epigallocatechin-3-gallate (EGCG), a polyphenol derived from green tea, on activator protein-1 (AP-1) components (phospho-c-Jun and c-Fos), cyclooxygenase-2 (COX-2) and heat shock proteins (HSPs) in the liver of heat-stressed quails. 2. A total of 180 5-week-old female Japanese quails were reared either at 22 degrees C for 24h/d (thermoneutral, TN) or 34 degrees C for 8h/d (heat stress, HS) for 12 weeks. Birds in both environments were randomly given 1 of 3 diets: basal diet and basal diet with 200 or 400mg of EGCG added per kilogram of diet. 3. The hepatic c-Jun, c-Fos, COX-2 and HSPs gene expression for quails reared under the HS environment was greater than those reared under the TN environment. Supplemental EGCG decreased hepatic expression of these proteins at a greater extent under HS than TN. 4. In conclusion, suppression of AP-1 COX-2 and HSPs may partly account for the inhibitory effect of EGCG in heat-stressed quail.
Keywords: Green Tea Polyphenol; Nf-Kappa-B; Lipid-Peroxidation; Vitamin-E; Broiler-Chickens; Shock Proteins; Ascorbic-Acid; Laying Hens; in-Vitro; Expression